Integrative Edu-Tourism Model of Salak Slebor (Sleman Bogor) through Demonstration Plots in Cimande Tourism Village: A Sustainable Tourism Approach - Maidar Simanihuruk; Laurinciana S Sampebatu; Mohd Noor Ismawi Ismail; Yuviani Kusumawardhani (Jurnal Penelitian Pariwisata, 2026)
The purpose of this study is to analyze the determinants of visitors’ behavioral intention and to formulate an integrative edu-tourism model based on the Salak Slebor demonstration plot in Cimande Tourism Village. A mixed-method approach was employed by combining quantitative analysis using multiple regression and qualitative exploration through focus group discussions, interviews, and participatory observation. The quantitative data involved 35 purposively selected respondents, while qualitative data were gathered from 10 key informants, including farmers, community leaders, and Pokdarwis members. The findings reveal that destination attractiveness (AT) and experiential engagement (ENG) significantly influence behavioral intention (BI), whereas educational value (EDU) and sustainability awareness (SUS) are not significant in partial tests. However, simultaneous regression confirms that all four variables together account for 62.9% of the variance in BI (R² = 0.629), indicating that the model has substantial explanatory power. Qualitative results further emphasize the strategic importance of EDU and SUS for long-term knowledge transfer, ecological sustainability, and cultural preservation. Integrating both findings, this study formulates the Integrative Edu-Tourism Model of the Salak Slebor Demonstration Plot, structured around four pillars: Agronomy, Education, Socio-Economic Participation, and Institution & Branding. Keywords: demonstration plots, destination attractiveness, educational value, experiential engagement, behavioral intention